Security, payment, and privacy for network commerce. - Neuman, B.C.
As the Internet is used to a greater extent in business, issues of protection and privacy will have more importance. Users and organizations must have the ability to control reads and writes to network accessible information, they must be assured of the integrity and confidentiality of the information accessed over the net, and they must have a means to determine the security, competence, and honesty of the commercial service providers with which they interact. They must also be able to pay for purchases made on the network, and they should be free from excessive monitoring of their activities. This paper discusses characteristics of the Internet that make it difficult to provide such assurances and surveys some of the techniques that can used to protect users of the network
Keywords: Internet; Business; Commercial service providers; Information confidentiality; Information integrity; Network accessible information; Network commerce; Payment; Privacy; Protection; Security